2020
DOI: 10.1016/j.psj.2019.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Protective efficacy of the Newcastle disease virus genotype VII–matched vaccine in commercial layers

Abstract: Newcastle disease virus ( NDV ) is a major threat to the poultry industry worldwide, with a diversity of genotypes associated with severe economic losses in all poultry sectors. Class II genotype VII NDV are predominant in the Middle East and Asia, despite intensive vaccination programs using conventional live and inactivated NDV vaccines. In Egypt, the disease is continuously spreading, causing severe economical losses in the poultry industry. In this study; the protective efficacy of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 53 publications
6
30
0
Order By: Relevance
“…This may be referred to the amount of antigen in each vaccine, with vaccine A containing a higher amount of antigen (350 HAU unit/dose), while vaccine B contained around 200 HAU unit/dose [38]. As previously reported by , increasing the dose from 200 to 250 or 350 HAU can improve the immune response and protection against H9N2 [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be referred to the amount of antigen in each vaccine, with vaccine A containing a higher amount of antigen (350 HAU unit/dose), while vaccine B contained around 200 HAU unit/dose [38]. As previously reported by , increasing the dose from 200 to 250 or 350 HAU can improve the immune response and protection against H9N2 [6].…”
Section: Discussionmentioning
confidence: 99%
“…), in addition to coccidia species. All these pathogens have caused severe economic losses and have badly affected the veterinary care strategies [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Avian influenza (AI) is a contagious viral disease, belonging to the Orthomyxoviridae family, and is a segmented, single-stranded, negative sense RNA virus [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It had been established that homologous genotype vaccines are more effective in preventing virus replication and shedding after challenge than heterologous NDV genotype VII vaccine [52,54,55]. However, Sultan et al [56] recommended the combined vaccination regime of inactivated genotype VII-matched and live genotype II vaccines for three times along the rearing period in commercial layers for better protection against clinical disease, mortality and viral shedding confirming the results of Sedeik et al [57]. The aforementioned authors reported that the use of either inactivated genotype VII or II once alone induced the insufficient protection against clinical disease, mortality, and viral shedding in broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…T he poultry industry is exposed to several threats such as of viral origin like avian Influenza, Newcastle disease, infectious bronchitis, infectious bursal disease, avian adenovirus, or of bacterial origin like the Salmonellae species, Escherichia coli, Clostridium spp. (Ayoub et al 2019, Diab et al 2019, Elhady et al 2018, Fawzy et al 2020, Sedeik et al 2018, Sultan et al 2019a, Sultan et al 2019b, Sultan et al 2020. Salmonella is one of the most serious bacterial pathogens as it is associated with economic losses in poultry farms in addition to the zoonotic effects.…”
Section: Introductionmentioning
confidence: 99%